Exploration and Inventory of Araceae Genera in Silui Mountain and Uluisimbone Forest, Kolaka Regency, South-East Sulawesi - BRAMANTYO TRI ADI NUGROHO; YESSI SANTIKA (Biodiversitas Journal of Biological Diversity, 2008)
The island of Sulawesi has been highlighted as a globally important conservation area, across a range of evaluation criteria. Collection rates on the Sulawesi Island are the lowest among in Indonesia area. Taxonomic study also has been limited, with most experts reporting large numbers of undescribed species. The research of Araceae diversity in Sulawesi is subject which in general has not been studiedcritically. The main purpose of this research is concerned to inventory the diversity of Araceae genera. The exploration was conducted in each location used exploring method. The Araceae genera in Silui Mountain and Uluisimbone forest consist of 30 numbers, 24 species and 14 genera, including into 3 sub families (Aroideae, Monsteroideae and Pothoideae). Mostly Araceae were found at humid location, the river flows. Schismatoglottis calyptrata Zoll. & Mor. and Aglaonema simplex Bl. are dominant species for terrestrial Araceae, where asScindapsus spp. and Pothoidium spp. are dominant species for climbing Araceae.Key words: Araceae, Silui, Uluisimbone, Sulawesi.